Determinants of Female Worker Productivity in Indonesia: Panel Data Analysis - Arvina Fastika Putri; Muhammad Anas (STIE Amkop Makassar, 2026)
Labor productivity is an important indicator in assessing the efficiency and quality of human resources in producing output and their contribution to the economy. This study aims to estimate the effect of the number of female workers, female education levels, female human development index, gender empowerment index, and female wage levels on female labor productivity in Central Java Province from 2019 to 2023 using panel data regression with the Fixed Effects Model (FEM) approach. The regression results show that the number of female workers has a negative effect on female labor productivity, while the level of female education, female human development index, gender empowerment index, and female wage levels have a positive effect on female labor productivity. Therefore, the government is expected to formulate policies that focus on improving the quality and empowerment of female labor through education, health, and gender equality, as well as strengthening production efficiency so that the increase in the number of female workers can be balanced with increased productivity